Antidiarrhoeal screening of Himalayan edible plant Begonia rubrovenia and its marker followed by its validation using computational analysis - Rupali S. Prasad; Jun M. Kalita; Nitish Rai; Nikhil Y. Yenorkar; Suhas R. Dhaswadikar; Pravesh Sharma; Mahaveer Dhobi; Damiki Laloo; Saurabh K. Sinha; Prakash R. Itankar; Satyendra K. Prasad (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background Diarrhoea has become one of the major areas of concern due to its high mortality rate contributing it to be the second largest cause of death in world. To explore the effectiveness of medicinal plant, the present investigation was undertaken to scientifically justify the traditional claim of the ethanolic root extract of the plant Begonia rubrovenia (EBV) against diarrhoea. Results EBV was standardized using HPLC with quercetin as marker and was further subjected to normal fecal excretion study at 100, 200 and 300 mg/kg, p.o. along with quercetin and loperamide. The study confirmed the effectiveness of EBV at 200 and 300 mg/kg followed by quercetin. In castor oil induced diarrhoea rat model, EBV at 200 and 300 mg/kg significantly delayed onset of diarrhoea, reduced the diarrhoeal faecal output which contributed in higher % protection. The effectiveness of EBV at 200 mg/kg was also confirmed through gastrointestinal motility, fluid accumulation and PGE2 induced enteropooling tests. EBV and its marker quercetin also reduced the elevated level of NO and cytokines and restored the alterations in antioxidant enzymes, ions and enhanced Na+/K+–ATPase activity. Molecular docking, dynamics and network pharmacology study confirmed the role of quercetin in modulating the inflammatory mediators IL-1β, TNF-α and EP3 prostanoid receptor, where quercetin formed more stable complex with EP3 prostanoid receptor. Conclusion The study has scientifically justified the traditional use of the plants B. rubrovenia in treating diarrhoea, where quercetin played a critical role in the observed antidiarrhoeal potential of B. rubrovenia contributing in maintaining electrolyte balance, antioxidant status and inhibiting inflammatory mediators.